SOME ISSUES OF IMPROVING ORGANIZATIONAL-LEGAL BASES OF BANKING LEGISLATION IN UZBEKISTAN (TSUL LEGAL REPORT, 2026)
In this article, the author analyzed the categories related to the banking system as part of the financial system. The purpose of this study is to develop proposals and conclusions aimed at improving the performance of the bank as a result of the study. Banks are active participants in the financial market and business entities. Proper implementation of banking activities leads to the development of production and entrepreneurship. Banks provide banking services to individuals and legal entities and ensure the circulation of their funds through the bank. Banks, in turn, are financial agents that determine the volume of working capital, determine the tax base for paying taxes, and provide a non-cash payment system. Therefore, it is important to carry out state registration of the activities of banks and ensure the legality of their activities. By studying these issues through a comparative analysis of domestic and foreign legislation, historical, legal, systemic, logical, statistical, and other methods, the concepts of banking and banking activities in national legislation and proposals for banking legislation have been developed. These proposals are used in scientific activities, lawmaking, law enforcement, the interpretation of banking legislation, and the improvement of national legislation. Banks carry out banking operations and banking services of a legal nature. Banking is concerned with finance and banking activities, while banking services are manifested in organizational activities.